Moving From GUIs to PUIs - Turk, Matthew (1998)
For some time, graphical user interfaces (GUIs) have been the dominant platform for human computer interaction. The GUI-based style of interaction has made computers simpler and easier to use, especially for office productivity applications. However, as the way we use computers changes and computing becomes more pervasive and ubiquitous, GUIs will not easily support the range of interactions necessary to meet users’ needs. In order to accommodate a wider range of scenarios, tasks, users, and preferences, we need to move toward interfaces that are natural, intuitive, adaptive, and unobtrusive. The aim of a new focus in HCI, called Perceptual User Interfaces (PUIs), is to make human-computer interaction more like how people interact with each other and with the world. This paper describes the emerging PUI field and then reports on three PUI-motivated components: computer vision-based techniques to visually perceive relevant information about the user.